Pendekatan Model Komunikasi, Partisipasi Kelompok dalam Adopsi Inovasi Agribisnis Ternak Kambing PE di Girikerto - Sleman Daerah Istimewa Yogyakarta - Hano Hanafi; Soemardjo Soemardjo; Amirudin Saleh; Ida Yuhana (Agro Ekonomi, 2004)
The essence of the participatory development is to encourage society to behave independently in all fields. This mean that it is need an interaction and interdependency ofall the parties involved in the development, including government, society and private institutions, to mobilise the energy and the sources given in the society. This research was conducted to support the implementation of innovation of PE sheep agribusiness in the group level in Girikerto, Sleman Regency. This research aimed at knowing the effective group communication model in the adoption and innovation of the PE sheep agribusiness, and to knowing the level of participation of the groups' members in the adoption and innovation of the PE sheep agribusiness.This research was conducted in Girikerto village, Turi Sub-regency, Sleman Regency of Yogyakarta Province in the period of August – November 2001. The analysis units in the research were individual members of breeder group of PE sheep in Girikerto village. The studied groups was set "purposively" with the consideration of the improvement level of breeder group in the implementation of the innovation of PE sheep agribusiness. The selected group was breeder group of "Pangestu" (as the relatively advanced breeder group) and the breeder group of "Sukorejo" (as the relatively less developed breeder group). The respondents who were selected as samples constitute of Pangestu group by 59 individuals, and the members ofSukorejo group were 21 individual. Then, the total respondents in this research were 80 individuals. This research conducted through survey in the 80 breeders. The variables studied were breeder characteristic, participatory level of the groups' member Data obtained was analysing using computer-based SPSS method.The result of the research suggesting that the communication model occurred in the breeder groups, in the adoption and innovation of the PE sheep, was throughout the interpersonal communication and small group communication, which frequently called group communication. Contact person from which the information derived was an opinion leader, who was the groups' chief followed by the groups' staff andfnally to all of the members of the groups. The adoption and the innovation of the PE sheep agribusiness in the breeder group was more effective with participatory model from all of the groups' members, beginning with the planning, and then the implementation, and finally the evaluation and the employment of the result, according to the knowledge, skill and the sources given in the area.